APPLICATION OF PARENTERAL NUTRITION IN PREMATURE INFANTS - N. P. Molokanova; L. K. Gavrikov ("Paediatrician" Publishers LLC, 2015)
Prematurity and, as a result, the expressed morphofunctional immaturity of all body organs and systems makes an essential contribution to morbidity and mortality rates. The efficiency of care for prematurely born children in many respects depends on adequacy of the enteral and parenteral nutrition program. The balanced and correctly organized nutrition is one of the most important components of care for the prematurely born children, which defines both immediate and remote prognosis. The review of literature on parenteral nutrition in prematurely born children is given. The main indications, dosages, beginning time, and strategies for the appointment of «aggressive» nutrition are specified. Main conclusion: it is necessary to use higher doses for parenteral nutrition, and take into account that an early appointment of amino acids and fatty emulsions is important. An early 'aggressive' nutrition strategy is well tolerated by preterm infants and provides proper rates of physical development in the postnatal period without adverse outcomes.